2019
DOI: 10.34172/jsums.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acceptance and commitment therapy on perceived stress, resilience, and the quality of life in thalassemia major patients

Abstract: Background and aims: The present study aimed to determine the effect of acceptance and commitment therapy on perceived stress, resilience, and the quality of life in thalassemia major patients in Lordegan during 2015-2016. Methods: This semi-experimental study used the pre-test and post-test designs with a control group and period. The samples included 40 patients with thalassemia major who referred to Lordegan Shohada hospital, were selected by the purposeful sampling technique based on the inclusion and excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Resilience can be seen in all kinds of behaviors, thoughts and actions throughout the life cycle [37]. Jabbarifard et al (2019) were the only ones who measured the impact of mindfulness-based cognitive therapy counseling on the resilience of patients with thalassemia and reported that mindfulness-based cognitive therapy reduced perceived stress, improved resilience and quality of life in patients with thalassemia [15]. Other researchers measured the impact of mindfulness-based stress reduction counseling on resilience in patients with cancer [24], systemic lupus erythematosus [26], vulnerable women [18], and employees [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience can be seen in all kinds of behaviors, thoughts and actions throughout the life cycle [37]. Jabbarifard et al (2019) were the only ones who measured the impact of mindfulness-based cognitive therapy counseling on the resilience of patients with thalassemia and reported that mindfulness-based cognitive therapy reduced perceived stress, improved resilience and quality of life in patients with thalassemia [15]. Other researchers measured the impact of mindfulness-based stress reduction counseling on resilience in patients with cancer [24], systemic lupus erythematosus [26], vulnerable women [18], and employees [38].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced resilience is another problem experienced by patients with thalassemia [3,15]. Resilience refers to maintaining proper functioning, avoiding underlying stressors, and successfully adapting to difficult life experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anak dengan thalasemia dapat mengalami berbagai perubahan pada dirinya, seperti perubahan penampilan anak, kelainan bentuk tulang, perawakan badan anak yang pendek, citra diri rendah, kunjungan yang sering ke rumah sakit untuk transfusi, tertunda atau tidak adanya perkembangan seksual, gangguan kesuburan, dan komplikasi lainnya yang terkait dengan penyakitnya seperti penyakit jantung, penyakit tulang, diabetes, infeksi, dan lain-lain (Meiyanti et al, 2020). Masalah psikologis pada anak dengan thalassemia yaitu merasa rendah diri, isolasi social, merasakan cemas terhadap penyakitnya, dan juga stress (Hakeem et al, 2018;Jabbarifard et al, 2019;Renylda, 2018).…”
Section: Pendahuluanunclassified
“…Psychosocial equilibrium in patients with b-TM is constantly threaten by concerns regarding life goals, expectation, and standard of life compared to non-affected peers (Ahmadi et al, 2020). In view of this, biopsychosocial components have gained increased interest in clinical research context and different psychological interventions have been promoted to increase b-TM patient quality of life (Gharaibeh et al, 2009; Jabbarifard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%